Does my personality affect my competency? The role of gender identification and career adaptability among hotel employees - Cop, Serdar; Alola, Uju Violet; Lasisi, Taiwo Temitope (Wiley, 2022)
The tourism industry is the fastest growing industry in the world amidst the increase in terrorism, climate change, political instability, and other indirect negative effects on tourism. In order to survive this vulnerable, evolving, and competitive market, it is important that employees put effort into ensuring the provision of satisfactory services to satisfy customers' demand. For this purpose, this research determines the effect of personality traits on career competency (career control, reflection on motivation, networking, work exploration, self-profiling, and reflection on qualities) with the mediating role of career adaptability (curiosity concern, confidence, and control) and moderating role of gender identification. Career construction theory and social identity theory were used to justify these relationships. A total number of 330 questionnaires were filled and after discarding incomplete ones, 311 were retained for analysis, yielding a response rate of 94.2%. Using Analysis of Moment Structure 22.0 and Statistical Packages for Social Sciences 20.0, to analysis the study, the findings aid managers and policymakers in designing the organizational roles and on-the-job training for employees. Moreover, the relationship between personality traits and career adaptability can serve as a blueprint in employee recruitment and provide a new insight into employee selection. Theoretical and practical implications were provided in the concluding part.
Keywords: Adapt-Abilities Scale; Mediating Role; Psychometric Properties; Big-5 Personality; Job-Satisfaction; Construction; Predictors; Incivility; Outcomes; Women